2018
DOI: 10.1007/s12035-018-1076-y
|View full text |Cite
|
Sign up to set email alerts
|

TNFα in the Trigeminal Nociceptive System Is Critical for Temporomandibular Joint Pain

Abstract: Previous studies have shown that tumor necrosis factor alpha (TNFα) is significantly increased in complete Freund's adjuvant (CFA)-treated temporomandibular joint (TMJ) tissues. However, it is unclear whether TNFα in the trigeminal nociceptive system contributes to the development of TMJ pain. In the present study, we investigated the role of TNFα in trigeminal ganglia (TG) and spinal trigeminal nucleus caudalis (Sp5C) in CFA-induced inflammatory TMJ pain. Intra-TMJ injection of CFA (10 μl, 5 mg/ml) induced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 37 publications
(43 reference statements)
3
37
0
Order By: Relevance
“…IL-1β is key cytokine and plays an essential role in the central sensitization and hyperalgesia [32]. The upregulation of TNF-α expression induced by an intra-temporomandibular joint CFA (Complete Freund's Adjuvant) injection in the Vc has been reported [33]. In our study, we observed high production of TNF-α, IL-1β, and IL-6 in response to pulp exposure, on day 21 after DPI.…”
Section: Neuroinflammatory Profile After Pulp Exposuresupporting
confidence: 60%
“…IL-1β is key cytokine and plays an essential role in the central sensitization and hyperalgesia [32]. The upregulation of TNF-α expression induced by an intra-temporomandibular joint CFA (Complete Freund's Adjuvant) injection in the Vc has been reported [33]. In our study, we observed high production of TNF-α, IL-1β, and IL-6 in response to pulp exposure, on day 21 after DPI.…”
Section: Neuroinflammatory Profile After Pulp Exposuresupporting
confidence: 60%
“…It is possible, however, that there may be site or model specific differences. MGS was only transiently elevated following Complete Freund's Adjuvant inflammation of the TMJ 38 , which does not have ongoing infection occurring in the model. In terms of change in the score, our data reflect a similar to slightly greater increase in MGS as compared to tooth movement 35 , and potentially within the lower end of ranges reported for an exogenous-CGRP migraine model 39 and neuropathic injury of the infraorbital trigeminal nerve 37 .…”
Section: Discussionmentioning
confidence: 90%
“…Recent study with functional neuroimaging has consistently demonstrated altered central pain perception in the brain of patients with FMS [ 5 ]. Accumulated studies have demonstrated that either orofacial inflammation or stress may affect the same areas specific for central pain processing and modulation [ 29 , 30 ]. In our comorbid pain model, we hypothesize that stress signal input could concurrently enhance or prolong the masseter muscle inflammation-induced neuronal hyperactivity in supraspinal pain pathway, integrally resulting in central sensitization in the spinal dorsal horn through the descending brainstem modulatory system.…”
Section: Discussionmentioning
confidence: 99%